MEAT SENSORY QUALITY RESULTING FROM QUAIL (Coturnix Coturnix Japonica) LAYER PHASE SUPLEMENTED WITH PAPAYA LEAF EXTRACT - Purwana, I Putu; Sudrajat, Deden; Dihansih, Elis (Jurnal Peternakan Nusantara, 2019)
The study was aimed at assessing the potential of papaya leaf extract as an herbal antibiotic used as a supplement in drinking water of quails (Coturnix coturnix japonica). Physical properties of meat including pH value, water holding capacity, cooking loss, and sensory properties including tenderness, taste, flavor, juiciness, color, and texture were measured. The study was conducted from 18 February to 18 March 2017. Quail birds aged 40-44 weeks were put in battery cages sized 128 cm x 60 cm x 167 cm. Treatments consisted of drinking water with no papaya leaf extract (control, R0), drinking water with commercial antibiotic of 0.5 g/l (R1), drinking water with papaya leaf extract of 10 ml/l (R2), drinking water with papaya leaf extract of 20 ml/l (R3), and drinking water with papaya leaf extract of 30 ml/l (R4). Drinking water was given ad libitum. A completely randomized design with 5 treatments and 5 replicates was used. Data were subjected to an analysis of variance and a Kruskal-Wallis test. Results showed that the inclusion of papaya leaf extract in drinking water no significant effects on physical quality of quail meat and consumer acceptance include aroma, taste, color, tenderness, juicenees and texture. Keywords: sensory quality, layer quail, papaya leaf extract.